1) (– 2) ∙ (– 13) =
2) (– 45) ∙ (+ 2) =
3)(– 17 + 2 + 19 – 3) ∙ (+ 25 – 8 + 1 – 26) =
4)(– 1 + 36 – 32) ∙ (– 8 + 52 – 41) =
5)(258 – 189 – 96) ∙ (– 279 + 421 – 156) =
6) – 2 ∙ [– 4 + 3 ∙ (– 29 + 3 + 28) – 2 ∙ (+ 14 – 15 + 2)] =
7) – 12 ∙ [– 17 + 15 ∙ (+ 59 – 27 – 30) – 21] =
8) – 139 ∙ [+ 711 – 394 ∙ (– 417 + 395 + 24)] =
9) + 2 ∙ {+ 5 ∙ [+ 28 – 2 ∙ (– 19 + 6 + 17)] – 23} =
10)– 11 ∙ {+ 18 ∙ (– 15) + 10 ∙ [(– 12) ∙ (+ 13) – (– 28 + 76) ∙ (+ 89 – 93)]
ajutor va rog am test in 40m
dau coroana si like
Răspunsuri la întrebare
Răspuns:
1) (-2)x(-13)=26
2) (-45)x(+2)=-90
3) (-17+2+19-3)x(+25-8+1-26)=(-15+19-3)x(17+1-26)=(4-3)x(18-26)=1x(-8)=-8
4) (-1+36-32)x(-8+52-41)=(35-32)x(44-41)=3x3=9
5) (258-189-96)x(-279+421-156)= (69-96)x(142-156)= -27x(-14)= 378
6) -2x[-4+3x(-29+3+28)-2x(+14-15+2)]
-2x[-4+3x(-26+28)-2x(-1+2)]
-2x[-4+3x2-2x1]=-2x[-4+6-2]= -2x0=0
7) -12x[-17+15x(+59-27-30)-21]=
-12x[-17+15x(32-30)-21]
-12x[-17+15x1-21]=-12x[-17+15-21]= -12x[-2-21]= -12x(-23)=276
8) -139x[+711-394x(-417+395+24)]
-139x[711-394x(-22+24)]
-139x[711-394x2]=-139x[711-788]=-139x(-77)=10703
9) +2x{+5x[+28-2x(-19+6+17)]-23}=
2x{5x[28-2x(-13+17)]-23}=
2x{5x[28-2x4]-23}=
2x{5x[28-8]-23}= 2x{5x20-23}=2x{100-23}=2x77=154
10) -11x{18x(-15)+10x[(-12)x(+13)-(-28+76)x(89-93)]}
-11x{-270+10x[-156-48x(-4)]}
-11x{-270+10x[-156+192]}
-11x{-270+10x36}=-11x{-270+360}=-11x90=-990
Explicație pas cu pas: